Underwater Distance Measurement: Precise Underwater Distance Measurement by Dual Acoustic Frequency Combs (Ann. Phys. 9/2019). Issue 9 (11th September 2019) - Wu, Hanzhong; Qian, Zhiwen; Zhang, Haoyun; Xu, Xinyang; Xue, Bin; Zhai, Jingsheng
Abstract : In article number1900283, Hanzhong Wu, Jingsheng Zhai, and co‐workers describe the successful generation of fully stabilized acoustic frequency combs. Well‐defined electromagnetic waves can be smoothly bridged with acoustic waves via a hydroacoustic transducer. Long distances are able to be measured underwater using the dual‐comb scheme, and the measurement uncertainty can achieve 50 µm. This work paves the way to future underwater applications using acoustic frequency combs.